(untitled) (Research, Society and Development, 2021)
The common bean is a crop of great food, economic and social importance, in terms of production and consumption, it is an herbaceous legume, with a cycle around 95 days. Most cultivars used for cultivation in the Brazilian market express great genetic variability as to the onset of flowering and total cycle length. Therefore, the objective of this work was to evaluate the morphological and agronomic characterization of common bean genotypes regarding the precocity of cultivation. The experiment was conducted in EMAPER, in the city of Cáceres-MT, adopting the experimental design in randomized blocks with three repetitions, evaluating 58 common bean genotypes. The plots were composed of four rows of 4 m, with spacing of 0.5 m between rows. The evaluated characteristics were the number of days to flowering and crop cycle, the data were subjected to analysis of variance and comparison of means by the Scott-Knott grouping test at 1% probability. The genetic divergence was estimated by Tocher’s optimization method and hierarchical UPGMA, based on the Generalized Mahalanobis Distance using the computer program GENES. It can be concluded that there is genetic variability among the evaluated common bean genotypes, and the genotypes 3 (BG-UNEMAT-11) and 57 (TB 02-23) showed fewer days to flowering (31 days) and shorter crop cycle (73 to 82 days), being the most suitable for breeding programs aiming precocity.